Ads to icons how advertising succeeds in a multimedia age - Springer, Paul (London Kogan Page, 2009)
The second edition of Ads to Icons examines current and future trends in advertising. Through 50 international case studies of new and iconic advertising campaigns, author Paul Springer identifies why these campaigns were successful and analyzes their contribution to the continued development of advertising.
Rethinking mass media -- Widening formats -- Events-driven -- Shaping product experiences -- Digital persuasion -- Online spaces -- The new media landscape -- The new job landscape -- Closer -- Where advertising stops--and marketing begins
Electronic reproduction.
Keywords: Advertising -- Case studies; Advertising campaigns -- Case studies; Electronic books